Philosophieren: Wider Theorie und Begründungszwang - Guzzoni, Ute, (Verlag Karl Alber, 2023)
“I think that the main interest of philosophy in our time should be to rethink our relationship to the world. According to the previous, two-thousand-year-old relationship of man, he saw himself confronted with a reality that he had to subjugate through mental and physical appropriation. Not least the realisation that nature cannot be dominated but threatens to strike back in extreme ways, as well as the experience of world-wide wars and the spreading exploitation of man by man, lead to the insight that our relationship to the Other must be reconsidered. I am not asking what philosophy is, but how philosophising happens - astonishing, critical, speculative, pictorial, finite.” (The author about her book)